2020
DOI: 10.4103/aer.aer_13_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of duration of analgesic effect of nalbuphine and morphine as an adjuvant to bupivacaine in the supraclavicular block under ultrasound guidance

Abstract: Background: Although many studies are available in the literature that has analyzed the effects of morphine, nalbuphine, and other opioids, no study had compared the effects of nalbuphine versus morphine as an adjuvant to bupivacaine in the supraclavicular block under the guidance of ultrasound. Methodology: A randomized, double-blinded, prospective study was carried out on 60 patients of the American Society of Anesthesiologists Class I and II who were undergoing upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In 161 studies, patients received a supraclavicular brachial plexus block, 26,29–160 in 40 studies, patients received an axillary brachial plexus block, 24,27,161–198 in 28 studies, an interscalene block was performed, 25,199–220 in 11 studies, patients received an infraclavicular brachial plexus block, 221–231 one study used a coracoid approach to brachial plexus block 232 and one study used a suprascapular combined with axillary nerve block 233 . A detailed description of included studies is presented in the supplemental content (supplemental table 3, http://links.lww.com/EJA/A839).…”
Section: Resultsmentioning
confidence: 99%
“…In 161 studies, patients received a supraclavicular brachial plexus block, 26,29–160 in 40 studies, patients received an axillary brachial plexus block, 24,27,161–198 in 28 studies, an interscalene block was performed, 25,199–220 in 11 studies, patients received an infraclavicular brachial plexus block, 221–231 one study used a coracoid approach to brachial plexus block 232 and one study used a suprascapular combined with axillary nerve block 233 . A detailed description of included studies is presented in the supplemental content (supplemental table 3, http://links.lww.com/EJA/A839).…”
Section: Resultsmentioning
confidence: 99%
“…A study by Vengadessane et al 21 has observed a longer duration of block and postoperative analgesia with a lesser dose of the drug (nalbuphine 50 µg/kg with 20 ml of 0.5% bupivacaine). This may be attributable to the use of ultrasound in their study.…”
Section: Discussionmentioning
confidence: 97%
“…Opioids belonging to mixed agonist-antagonists like butorphanol and nalbuphine have also been used as adjuvants to local anesthetics in several studies with favorable results [18][19][20][21][22][23][24] . Pentazocine belongs to a mixed agonist-antagonist opioid-like nalbuphine and butorphanol 4,25 but no study to date has used pentazocine as an adjuvant to local anesthetic in brachial plexus block.…”
Section: Discussionmentioning
confidence: 99%
“…Nalbuphine, a new type of synthetic opioid, is frequently used to treat moderate pain, which exhibits analgesic effects similar to morphine. 31 It has a better safety profile with milder μ receptor-related adverse effects and lower dependence compared with other opioids, as it is primarily a κ agonist and a partial μ antagonist. 32,33 In the present study, our results showed that the pain scores over the 24 hours in the nalbuphine group did not differ from that of the control, except for the first 2 postoperative hours, which can be explained by a half-life of 2 to 5 hours after nalbuphine intravenous injection.…”
Section: Discussionmentioning
confidence: 99%